(untitled) (World Science, 2018)
The article is devoted to the problem of introduction of new models of TV business monetization in the process of integration of television resumes on the Internet. Traditional television experiences one of the most difficult periods of its existence in the era of digital technology. Ukrainians are increasingly using the Internet to access television content. Video on Demand (VoD) is gradually becoming a new video consumption paradigm. The consumer adjusts the view for himself takes into account his advantages. Television managers need to figure out the weakest and strongest media points and should answer questions. How to prevent the process of passing the audience to the Internet? What alternative resources can be offered to TV audiences? What are the ways to monetize TV content when known business models are outdated?